Corrosion inhibition performance of 4-(prop-2-ynyl)- [1, 4]-benzothiazin-3-one against mild steel in 1 M HCl solution: Experimental and theoretical studies. (26th July 2021) - Benhiba, F.; Sebbar, N.K.; Bourazmi, H.; Belghiti, M.E.; Hsissou, R.; Hökelek, T.; Bellaouchou, A.; Guenbour, A.; Warad, I.; Oudda, H.; Zarrouk, A.; Essassi, E.M.
Abstract: 4-(prop-2-ynyl)-2H [1, 4]-benzothiazin-3(4H)-one (PBO) was synthesized and evaluated on corrosion resistance for mild steel (MS) in1 M HCl environment. The molecular and crystal structure of PBO has been determined by single-crystal X-ray crystallography, Hirshfeld surface (HS) analysis was carried out by using Crystal Explorer 17.5. Electrochemical impedance spectroscopy (EIS) and potentiodynamic polarization (PDP) techniques were used to find corrosion rate (CR) and corrosion inhibition efficiency (η) in the presence and absence of PBO. These techniques were supported with energy dispersive X-ray (EDX) and scanning electron microscope (SEM). Molecular Dynamics Simulation (MDS) and Frontier Molecular Orbital (FMO) are realized by means of the Density Functional Theory (DFT) method. The results show that PBO could offer an inhibition efficiency of 92% at 303 K. The type of inhibition mechanism of PBO was mixed-type. The Langmuir isotherm proved the highest compliance with experimental data, representing the generation of protective mono-layer of inhibitors on the MS substrate. The SEM pictures displayed a metallic substrate covered with a highly compact protective layer covered. The theoretical findings suggested by electronic/atomic computer simulations supported the inhibitive chemicals interfacial adsorption through reactive centres. Highlights: The anticorrosion process of PBO was evaluated by Research methods (Hirshfeld surface analysis, EIS and PDP). Surface analysis of mild steel was examined by SEM/EDX. Adsorption of PBO obeyed the Langmuir adsorption isotherm model. The adsorption process was discussed by DFT and MD simulation studies.